Evaluation of pour-on by Ethiopian farmers - Swallow, B.M.; Mulatu, W.; Leak, S.G.A. (OAU/STRC, 1995)
Since April 1990 a tsetse control experiment with the synthetic pyrethroid Ectopour has been conducted in the Gullele-Tolley area of the Ghibe Valley, southwest Ethiopia. Monthly applications of the pour-on were given to about 2,000 cattle between April 1991 and July 1992 and about 3,000 cattle between July and November 1992. Since December 1992 the treatments have been made available to all farmers in the area on a cost recovery basis. Formerly the treatments were free to selected farmers. A survey of 200 household heads who keep cattle in the control area was conducted to assess the impact of the price increase on farmer's demand for the treatments. Respondents to the household survey were asked about the advantages of the pour-on. Farmers noted a variety of advantages such as less trypanosomiasis (gendi), fewer problems with ticks, the animals graze well and quietly, cows are quieter when milking, there are fewer problems with ox peckers bothering the animsl, and the animals' wounds heal faster.